Domestic visitors’ expenditure and behavioural intention at International sports events: The case of the 2018 Asian Games - Mohamad Dian Revindo; Amalia Adininggar Widyasanti; Nalendro Nusantoro; Chairina Hanum Siregar; Naifa Dedya Mumtaz (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study examines domestic visitor expenditure and behavioural intentions during the 2018 Asian Games in Indonesia, focusing on short-term economic impacts and long-term event support. The primary data was collected through a survey of 401 domestic respondents, including athletes, officials, journalists, spectators, and local committees in Jakarta, West Java and Palembang. The research analyses spending levels, expenditure composition, and satisfaction with event aspects such as facilities, transportation, accommodation, security, and information access. Results indicate substantial variation in spending across respondent categories, with national athletes recording the highest average expenditure, while spectators largely spent on food, beverages, and souvenirs. Demographic factors, including age, gender, and event location, also influenced total spending. Despite satisfaction with sports venues and security, respondents reported notable concerns regarding transportation, access to information, and telecommunications. National pride was high, although support for hosting future mega-events was evenly divided, suggesting mixed perceptions of long-term benefits. The findings highlight the role of domestic tourism in mega-sport events and provide practical implications for event management, especially in improving visitor information systems and mobility services. This study contributes to the growing literature on sports tourism in emerging economies by addressing domestic spending determinants and behavioural intentions toward future event hosting.